Dynamics of Expression of Programmed Cell Death Protein-1 (PD-1) on T Cells After Allogeneic Hematopoietic Stem Cell Transplantation - Simonetta, Federico; Pradier, Amandine; Bosshard, Carine; Masouridi-Levrat, Stavroula; Dantin, Carole; Koutsi, Aikaterini; Tirefort, Yordanka; Roosnek, Eddy; Chalandon, Yves (Frontiers in Immunology, 2019)
Immune exhaustion contributes to treatment failure after allogeneic hematopoietic stem cell transplantation (HSCT) for hematological malignancies. Immune checkpoint blockade, including programmed cell death protein-1 (PD-1) blockade, is a promising strategy to improve the antitumor effect of allogeneic HSCT with high rates of response reported in patients treated for disease relapse. However, severe and sometimes fatal Graft- vs.-Host-Disease (GvHD) has been reported as a complication. Little is known about the dynamics of PD-1 expression on immune effector cells after allogeneic HSCT. In the present study, we analyzed PD-1 expression on T cell subpopulations isolated from 105 allogeneic HSCT recipients. Our analysis revealed a significant increase in proportions of PD-1-expressing CD4 and CD8 T cells early after allogeneic HSCT followed by a progressive normalization of PD-1 expression at CD8 but not CD4 T cell surface. Analysis of co-expression of two other exhaustion markers, 2B4 and CD160, revealed a preferential expansion of PD-1-single positive cells. Moreover, the analysis of granzyme B and perforin expression in PD-1+ and PD-1- CD8 T cells from HSCT recipients did not reveal any impairment in cytotoxic molecules production by PD-1-expressing CD8 T cells. Analyzing the association between clinical factors and the expression of PD-1 on T cells, we identified the use of in vivo and/or ex vivo T-cell depletion as the factor most strongly associated with elevated PD-1 levels on T cells. Our results extend our knowledge of the regulation of PD-1 expression at T cell surface after allogeneic HSCT, a crucial information for the optimization of post-transplantation PD-1 blocking therapies.